Can the digital economy promote urban green economic efficiency? Evidence from 273 cities in China - Huang, Lu; Zhang, Hongfeng; Si, Hongyun; Wang, Haoyu (Ecological indicators, 2023)
•• The green economic efficiency (GEE) is measured through a super-efficient SBM model.•• The digital economy development level is calculated by principal component analysis.•• The digital economy has a positive effect on urban GEE.•• Mechanisms base on marketization, industry, innovation and energy are detected.•• The effects vary between different urban location, scale and environmental regulation intensity. The development of the digital economy has changed human lifestyles and production and provided a new approach to achieving the United Nations Sustainable Development Goals (SDGs). As an important indicator reflecting both economic growth and ecological protection, the green economic efficiency (GEE) indicator is employed to express the level of sustainable development. By building an indicator system, introducing carbon dioxide emissions as an unexpected output and using a super-efficient slack-based measure (SBM) model, the the GEE of 273 cities in China are calculated. The development level of digital economy is calculated through principal component analysis (PCA). Unlike previous provincial-level studies, this study focuses on analyzing at the urban level. This study then uses a fixed effect model to analyze the effect of the digital economy on urban GEE. Based on various aspects, the transmission mechanisms of the digital economy on GEE have also been deeply analyzed. The results indicate that the digital economy has a positive effect on GEE. This conclusion is validated by endogeneity analysis and other robustness tests. The digital economy has a positive influence on urban GEE in Eastern, Central and Northeastern China. In large cities, medium-sized cities and cities with stricter governmental environmental regulations, the effect of the digital economy on GEE is more prominent. The mechanism analysis indicates that the digital economy mainly promotes urban GEE through the technological innovation effect, industrial structure optimization, energy structure transformation and market-oriented development. This study clarifies the role of the digital economy in advancing GEE and provides a reference to promote ecological development in developing countries.